Tumor seeding across specialties: a systematic review - Kipnis, Pavel; Ramanathan, Diya; Hoehn, Richard; Jethwa, Ashok R.; Karakla, Daniel W.; Rohr, Bethany; Sutter, Christopher M.; Mark, Jonathan R.; Khaja, Sobia F.; Li, Shawn; Thuener, Jason; Carroll, Bryan T. (Frontiers in Oncology, 2024)
BackgroundUnderstanding shared characteristics underlying reported tumor seeding episodes can reveal when tumor seeding is most likely to occur and guide clinical decision making. Our goal was to systematically review tumor seeding across specialties and determine what types of instrumentation and primary tumor histology are associated with tumor seeding.MethodsA systematic review was conducted using PubMed and Web of Science, per PRISMA guidelines. Publications ranged from 1965 to 2022, and studies with five or more reports of seeding were included. Papers were sorted by specialty and assigned a PRISMA Level of Evidence, and data analysis was conducted based on whether each paper supported the clinical significance of seeding.Results7,165 papers were screened with 156 papers included for analysis. Overall, there were 8,161 cases of tumors seeding across specialties with the majority from general surgery, gastroenterology, and urology. Laparoscopy (n=1,561) and needle biopsy (n=3,448) were most frequently implicated, and carcinomas (n=5,778) and adenocarcinomas (n=1,090) were the most common primary tumor types.DiscussionUpon review of the most updated (2023) versions of the NCCN and NICE guidelines across all cancer types, there were identified gaps in the coverage of tumor seeding within these guidelines, with tumor seeding being entirely absent from certain guidelines and partially absent from others.ConclusionsGiven the high cumulative reports of seeding and the deadly and disseminated nature of secondary disease, it is important to consider seeding risk when manipulating tumors and to modify current cancer care guidelines (NCCN/NICE) to ensure that they appropriately address seeding risk.